Benchmarking single-arm studies against historical controls from non-small cell lung cancer trials – an empirical analysis of bias. (2nd January 2020) - Snyders, Kelli; Cho, Doah; Hong, Jun Hee; Lord, Sally; Asher, Rebecca; Marschner, Ian; Lee, Chee Khoon
Abstract: Background: Recent trials of novel agents in 'rare' molecular subtypes of non-small cell lung cancer (NSCLC) have used single-arm trial designs and benchmarked outcomes against historical controls. We assessed the consistency of historical control outcomes using docetaxel data from published NSCLC randomized controlled trials (RCTs). Material and methods: Advanced NSCLC RCTs including a docetaxel monotherapy arm were included. Heterogeneity in tumor objective response rates (ORRs), progression-free survival (PFS) and overall survival (OS), and correlations between outcomes and year of trial commencement were assessed. Results: Among 63 trials ( N  = 10, 633) conducted between 2000 and 2017, ORR ranged from 0% to 26% ( I 2  = 76.1%, p heterogeneity  < .0001). Mean of the median PFS was 3.0 months (range: 1.4–6.4), 3-month PFS ranged from 25% to 85% ( I 2  = 86.0%, p heterogeneity  < .0001). Mean of the median OS was 9.1 months (range: 4.7–22.9), 9-month OS ranged from 23% to 79% ( I 2  = 83.0%, p heterogeneity  < .0001). Each later year of trial commencement was associated with 0.3% ( p  = .046), 0.5% ( p  = .11) and 0.9% ( p  = .001) improvement in ORR, 3-month PFS and 9-month OS rates, respectively. Conclusions: There was significant heterogeneity and an improving trend in docetaxel outcomes across trials conducted over 20 years. Benchmarking biomarker-targeted agents against historical controls may not be a valid approach to replace RCTs. Innovative study designs involving a concurrent control arm should be considered.